OPTIMIZING EMPLOYEE PERFORMANCE: THE IMPACT OF TRAINING AND DEVELOPMENT, WORK-LIFE BALANCE, AND WORKPLACE HAPPINESS - Rini Juni Astuti; Fika Amanda Febrianti (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Human resources are important and primary in every company, because if the company experiences an increase it is based on competent human resources. Strategic human resource management (HRM) must allow adaptation of HRM practices, namely knowledge and behavior in employees based on organizational needs. In this study, there is a phenomenon that employees work suboptimally and feel unable to complete their performance which results in decreased performance. In addition, the results of inconsistencies in previous studies, which examined employee performance. Thus, this study contributes to analyzing the influence of training and development, work life balance, and happiness at work on employee performance. Multiple linear regression analysis to test the proposed hypothesis, the number of data used was 130 employees in peanuts manufacturing in Pati, Central Java, Indonesia. The findings show that employee performance is affected by training and development, work-life balance, and happiness at work. Employees feel that these programs not only help improve their performance but also increase their satisfaction, pride, and motivation to work more effectively. Therefore, organizations need to continue to strengthen these programs in order to improve overall employee performance.